Case Report: Adjuvant Radiotherapy Can Be an Effective Treatment for Intimal Sarcoma of the Heart - Romanowska, Anna; Lewicka, Ewa; Sławiński, Grzegorz; Jankowska, Hanna; Zaucha, Renata (Frontiers in Oncology, 2021)
Intimal sarcoma of the heart is a sporadic disease, which involves symptoms of cardiac insufficiency due to a fast-growing intraluminal mass. Tumor resection is the first-line treatment, although its location precludes excision with wide uninvolved margins. Despite the aggressiveness of this neoplasm and a high risk of recurrence even after removal by microscopically radical surgery, no standard adjuvant therapy has been established. Chemotherapy is used either as an adjuvant treatment or in cases of advanced disease. In contrast, the use of radiotherapy is rare and usually considered in a palliative setting because the risk of radiation-induced heart disease after high-dose radiotherapy to the heart is significant. Herein, we present the cases of two patients, both diagnosed with cardiac intimal sarcoma, who received irradiation after tumor resection. In both cases, radiotherapy was effective, providing long-lasting local disease control. We regularly monitored cardiac function in both patients to assess the impact of radiotherapy on tumor-free heart structures. The excellent local control of the disease with only mild long-term cardiac dysfunction in both patients suggests that radiotherapy can be a useful treatment modality in this indication.